Comparison of cystatin C and Beta‐2‐microglobulin kinetics in children on maintenance hemodialysis. (17th October 2013) - Marsenic, Olivera; Wierenga, Andrea; Wilson, Donna R.; Anderson, Michael; Shrivastava, Tripti; Simon, Garfield A.; Beck, Anne M.; Swanson, Tiffany J.; Studnicka, Kathleen; Elberg, Dorit; Singh, Nisha S.; Couloures, Kevin; et al.
Abstract: Middle‐molecules (MM) are not monitored in children on hemodialysis (HD), but are accumulated and increase the risk of cardiovascular disease and mortality. Molecular properties of Cystatin C (CyC), 13 kDa, potentially make it a preferred MM marker over Beta‐2‐Microglobulin (B2M), 12 kDa. We compared CyC and B2M kinetics to investigate if CyC can be used as preferred MM marker. CyC (mg/L) and B2M (μg/mL) were measured in 21 low‐flux HD sessions in seven children. Blood samples were taken at HD start (pre), 1 and 2 hours into HD and at end of HD (post) for all sessions and 60 minutes after the first HD (Eq). PreCyC (9.85 ± 2.15) did not differ (P > 0.05) from postCyC (10.04 ± 2.83). PostB2M (38.87 ± 7.12) was higher (P < 0.05) than preHD B2M (33.27 ± 7.41). There was no change in CyC at 1 and 2 hours into HD, while B2M progressively increased. CyC or B2M changes did not significantly correlate with spKt/V (2.09 ± 0.86), ultrafiltration (4.61 ± 1.98%) or HD duration (218 ± 20 minutes). EqCyC was not different from postCyC (11.07 ± 3.14 vs. 10.71 ± 2.85, P > 0.05), while EqB2M was lower than postB2M (36.48 ± 7.68 vs. 41.09 ± 8.99, P < 0.05). MMs as represented by B2M and CyC are elevated in children on standard HD. Intensified HD modalities would be needed for their removal. B2M is affected by the dialytic process with a rise during HD independent of ultrafiltration and decrease 1 hour after, while CyC remains unchanged. We suggest that CyC be used as preferred marker of MM removal and as a marker of adequacy of intensified HD regimens.